The E3 Ubiquitin Ligase CRL5 Regulates Dentate Gyrus Morphogenesis, Adult Neurogenesis, and Animal Behavior - Reyes, Raenier V.; Hino, Keiko; Canales, Cesar Patricio; Dickson, Eamonn James; La Torre, Anna; Simó, Sergi (Frontiers in Neuroscience, 2022)
The dentate gyrus (DG) is an essential part of the hippocampal formation and participates in the majority of hippocampal functions. The DG is also one of the few structures in the mammalian central nervous system that produces adult-born neurons and, in humans, alterations in adult neurogenesis are associated with stress and depression. Given the importance of DG in hippocampal function, it is imperative to understand the molecular mechanisms driving DG development and homeostasis. The E3 ubiquitin ligase Cullin-5/RBX2 (CRL5) is a multiprotein complex involved in neuron migration and localization in the nervous system, but its role during development and in the adult DG remain elusive. Here, we show that CRL5 participates in mossy fiber pruning, DG layering, adult neurogenesis, and overall physical activity in mice. During DG development, RBX2 depletion causes an overextension of the DG mossy fiber infrapyramidal bundle (IPB). We further demonstrate that the increased activity in Reelin/DAB1 or ARF6 signaling, observed in RBX2 knockout mice, is not responsible for the lack of IPB pruning. Knocking out RBX2 also affects granule cell and neural progenitor localization and these defects were rescued by downregulating the Reelin/DAB1 signaling. Finally, we show that absence of RBX2 increases the number neural progenitors and adult neurogenesis. Importantly, RBX2 knockout mice exhibit higher levels of physical activity, uncovering a potential mechanism responsible for the increased adult neurogenesis in the RBX2 mutant DG. Overall, we present evidence of CRL5 regulating mossy fiber pruning and layering during development and opposing adult neurogenesis in the adult DG.